Physapubescin, a natural withanolide as a kidney-type glutaminase (KGA) inhibitor. Issue 5 (1st March 2017) - Cheng, Li; Wu, Can-Rong; Zhu, Li-Han; Li, Hua; Chen, Li-Xia
Graphical abstract: Highlights: The virtual ligand screening identified physapubescin as an inhibitor of KGA. Enzyme inhibition and cell-based assays confirmed its inhibitory effects on KGA. Physapubescin showed stronger toxicity to erlotinib-resistant HCC827-ER cells. Physapubescin was proved to be the first natural KGA inhibitor. Abstract: Kidney-type glutaminase (KGA) is over expressed in many kinds of cancers that converts glutamine to glutamate for supplying energy, and has become an object for targeted cancer therapy. The structure-based virtual ligand screening identified physapubescin, a withanolide purified from Physalis pubescens L., as a possible inhibitor of KGA with low binding energy. Enzyme inhibition experiments and cell-based assays further confirmed its inhibitory effects on KGA activity, suggesting potential applications of physapubescin and its derivatives as KGA inhibitors.